Instructional Communication Strategy for the Higher Education in the VUCA Era (Universitas Terbuka, 2023)
In recent years, we have been faced with conditions that are volatile, uncertain, complex, and ambiguous (VUCA), this is also felt by higher education institutions. The development of new technologies, changing student demographics, and shifting economic conditions all contribute to this dynamic environment. Under these conditions, the role of effective strategic communication is increasingly needed. Through this article, we will look at communication strategies that higher education institutions can use to navigate the VUCA era, one of which is the implementation of interactions between lecturers and students through online tutorials held for two months each semester. The main problem is the weakness of instructional communication between the tutor and student in the tutorial process. Several topics of discussion focus on how to manage and plan a communication crisis, utilize digital communication channels, foster a mindset of collaboration and cooperation, get to know the stakeholders, and be ready for changes in communication patterns in this VUCA era. In the end, with the basic concept of several theories, it can be concluded that the VUCA era is a challenge that higher education institutions must face. An effective communication strategy will help tertiary institutions monitor the environment, achieve their educational goals, and be better prepared in the VUCA era.